Self-medication practices among Malaysian older adults during the Covid-19 pandemic - Akkawi, Muhammad Eid; Elnaem, Mohamed Hassan; Nahas, Abdul Rahman Fata (Hong Kong Geriatrics Society and Hong Kong Association of Gerontology, 2023)
Objective. To assess the prevalence, patterns, and associated factors of self-medication among Malaysian older adults, and to investigate the impact of COVID-19 pandemic on self-medication. Methods: Between January and June 2021, Malaysian older adults aged ≥60 years were invited to participate in this cross-sectional study. A self-administered questionnaire was used to assess self-medication knowledge, perceptions, and practices before and during the pandemic. Results: Of 170 participants, 122 (71.8%) reported self medication. Common reasons for self-medication were a perception that the condition was minor and previous experience with the same problem. The main symptoms managed by self-medication were sore throat (56.9%), fever (56%), and headache (53.2%). The most commonly used medications were paracetamol (79.8%), analgesic patches (52.3%), and cough medications (47.7%). Most participants were unaware of possible drug-drug/drug-food interactions involving their medications. 33.6% of participants changed their self-medication practices during the pandemic; 65% of them consumed more vitamins and supplements to boost their health. Conclusion: Self-medication for minor ailments is prevalent among Malaysian older adults. Analgesics were the most commonly used medication. 33.6% of participants modified their self-medication practices during the COVID-19 pandemic; 65% of them consumed more vitamins and supplements to boost their health.